On the mechanical design of cruciate ligaments based on polymeric ropes of knee prothesis - Rodríguez Lelis, J. M.; Méndez Aguirre, J.S. A.; Arellano Cabrera, J. A.; Navarro Torres, J.; Vargas Treviño, M.; Pliego, A. A. (Revista Mexicana de Ingenieria Biomedica, 2011)
The cruciate ligaments are the ligamentous structure of the knee, which function as a joint stabilizer. It is known that the anterior cruciate ligaments are the most commonly injured ligaments of the knee, and are typically removed during total knee replacement. Also, that exists a limitation of existing grafts which has have motivated the investigation of tissue-engineered anterior cruciate ligament grafts. These investigations include different types of scaffold design. Although these designs have exhibited comparable behavior as natural anterior cruciate ligaments, still there is no commercially available synthetic graft that could achieve fully the mechanical properties of natural ones. In this paper it is attempted to accomplish this goal by introducing the design of cruciate ligaments based on the similarity between the mechanical behavior of the cruciate ligaments and the mechanical behavior of bridge cables, which allows one to apply the theory of the latter to propose an arrangement of braided threads of polyethylene and polypropylene. Mechanical tests on the proposed model show that the mechanical behavior of the designed cables is similar to the cruciate ligaments. The observed differences in stress-strain curves showed an average error of 10.08% for the anterior cruciate ligaments ACL and 9.99% for the posterior cruciate ligaments PCL.